Correction: Thermodynamically stable vesicle formation of biodegradable double mPEG-tailed amphiphiles with sulfonate head group. Issue 65 (2nd November 2020) - Ghosh, Rita; Dey, Joykrishna; Kumar, B. V. N. Phani
Abstract : Correction for 'Thermodynamically stable vesicle formation of biodegradable double mPEG-tailed amphiphiles with sulfonate head group' by Rita Ghosh et al., RSC Adv., 2020, 10, 32522–32531, DOI: ; 10.1039/D0RA05613H